2018
DOI: 10.1002/jsfa.9207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding strategies during lactation and the inclusion of quebracho in the fattening on performance and carcass traits in light lambs

Abstract: The feeding strategies during lactation had an effect on the carcass characteristics, highlighting the importance of the dam's diet during this period. The inclusion of quebracho in the lamb's concentrate had minor effects. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
2
6
0
1
Order By: Relevance
“…Then, the effects might be greatly dependent on the source of CT. In the present study, the lower α-tocopherol concentration at slaughter in the plasma of lambs fed the quebracho concentrate because the content of α-tocopherol was greater in aforementioned concentrate and moreover, its intake was also higher than that of the control concentrate [ 18 ]. In cows, it has been shown that 1% grape seed and grape marc meal extract, containing CT, increased the retinol concentration in the plasma but did not affect the β-carotene and α-tocopherol content in the plasma of lactating cows [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, the effects might be greatly dependent on the source of CT. In the present study, the lower α-tocopherol concentration at slaughter in the plasma of lambs fed the quebracho concentrate because the content of α-tocopherol was greater in aforementioned concentrate and moreover, its intake was also higher than that of the control concentrate [ 18 ]. In cows, it has been shown that 1% grape seed and grape marc meal extract, containing CT, increased the retinol concentration in the plasma but did not affect the β-carotene and α-tocopherol content in the plasma of lactating cows [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies correctly classified 100% of the carcass into their feeding system using the absolute valor of the integral of the translated spectra as estimators of carotenoids of perirenal fat [ 39 , 48 ]. Nevertheless, the discrimination of the lambs in the present study using subcutaneous and perirenal fat color parameters showed lower accuracy than using the content of retinol and tocopherols in both fat deposits because the finishing period on concentrates interfered [ 18 ]. Another possibility for tracing the maternal feeding could be the use of fatty acids of the meat, which allowed an 82–100% accuracy in the discrimination among suckling lambs whose dams were fed hay or fresh pasture supplemented with concentrates with or without quebracho [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The silt loam soil at the site had pH 8.1 and 1.81% organic matter and contained 16% clay, 53.5% silt, and 30.5% sand. Alfalfa and sainfoin were cultivated and managed as described by Lobón et al [15]. Samples of forage were collected fortnightly from 14 April to 22 September 2015.…”
Section: Methodsmentioning
confidence: 99%